2021
DOI: 10.24059/olj.v25i1.2470
|View full text |Cite
|
Sign up to set email alerts
|

Jordanian University Students’ Views on Emergency Online Learning During COVID-19

Abstract: The present study investigates the influence of digital technology, instructional and assessment quality, economic status and psychological state, and course type on Jordanian university students’ attitudes towards online learning during the COVID-19 emergency transition to online learning. A survey of 4,037 undergraduate students representing four Jordanian public and private universities revealed that personal challenges (such as economic and psychological stress) decreased students’ willingness to learn onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 14 publications
2
86
1
3
Order By: Relevance
“…The reasons for academic concerns are increased workload (Realyvásquez-Vargas et al, 2020 ; Aristovnik et al, 2020 ; Mishra et al, 2020 ), the volume of assignments (Al-Salman & Haider, 2021 ) lack of proper guidance (Ali, 2020 ; Sullivan et al, 2018 ). All these factors were significant based on the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reasons for academic concerns are increased workload (Realyvásquez-Vargas et al, 2020 ; Aristovnik et al, 2020 ; Mishra et al, 2020 ), the volume of assignments (Al-Salman & Haider, 2021 ) lack of proper guidance (Ali, 2020 ; Sullivan et al, 2018 ). All these factors were significant based on the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, many students have not benefited from online learning since they have not received proper guidance from their teachers (Ali, 2020 ; Sullivan et al, 2018 ) and lose interest in attending classes online. Also, Al-Salman and Haider ( 2021 ) stated that the volume of assignments has negatively affected students' academic performance. In another study, Aristovnik et al ( 2020 ) analyzed how students perceive the impact of the COVID-19 pandemic with a sample of 30,383 university students from 62 countries; their study revealed that students complained about the intensive workload that affected students' academic performance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Online education is convenient for students, where they can access online materials for 24 h (Stern, 2020). Online education turns education to be student-centered, where students take part in the learning process, and teachers work as supervisors and guides for students (Al-Salman et al, 2021).…”
Section: Online Learningmentioning
confidence: 99%
“…Therefore, it is expected that the present study will help bridge this gap by investigating the effect of using YouTube videos in improving Jordanian university students’ speaking skills. Furthermore, the need for conducting such a study in the Jordanian context has become so pressing due to the shift to the online teaching-learning model brought by the COVID-19 pandemic ( Al-Salman and Haider, 2021b ).…”
Section: Introductionmentioning
confidence: 99%